Case Report: Newborns With Pseudohypoaldosteronism Secondary to Excessive Gastrointestinal Losses Through High Output Stoma - Ou, Chia-Yu; Chen, Yen-Ju; Lin, Geng-Bai; Chen, Mei-Fan; Chia, Shu-Ti (Frontiers in Pediatrics, 2021)
Life threatening electrolyte imbalance is not uncommon in preemies. Differential diagnosis was important for immediate treatment. The syndrome of pseudohypoaldosteronism (PHA) is characterized by increased aldosterone secretion associated with clinical signs of hypoaldosteronism reflecting mineralocorticoid resistance. There are type I, type II and secondary type of PHA. Most secondary PHA reported in pediatric population resulted from urinary infection and obstructive uropathy and extremely rare from gastrointestinal fluid loss. Seven premies accepted jejunostomy or ileostomy, and they suffered from high output stoma. Electrolyte imbalance with bodyweight loss or cardiac event was noted. We found a high-level of aldosterone and renin and diagnosed them with secondary PHA due to excessive gastrointestinal losses. After stomal reversal, aldosterone and renin level became normalized and electrolyte was corrected.This study reporting the finding of secondary pseudohyperaldosteronism (hyponatremia, hyperkalemia and metabolic acidosis) in a series of cases with intestinal resection and ostomy of different causes. Early stomal reversal was recommended.